Incorporating Gamified Elements into Mobile Learning to Enhance Critical Thinking Skills - Sulisworo, Dwi; Maryani, Ika; Mastul, Al-Rashiff Hamjilani; Kusumaningtyas, Dian Artha (FKIP Universitas Lampung, 2024)
Abstract: Incorporating Gamified Elements into Mobile Learning to Enhance Critical Thinking Skills. Objective: This study explores the potential of gamified mobile learning in fostering critical thinking skills among learners. The objective is to investigate how gamified learning environments can provide engaging challenges, opportunities for decision-making, constructive feedback, collaborative experiences, adaptive pathways, and immersive narratives to promote the development of critical thinking skills. Methods: The research employed a descriptive qualitative approach to explore how gamified learning environments influence the development of critical thinking skills. This method aimed to express experiences, perceptions, and behaviors within their natural context. It was informed by a review of existing literature on gamified learning and critical thinking, establishing a theoretical framework and grounding the research in established theories and findings. Thematic analysis was used to identify patterns and themes in the data, which were then integrated with relevant literature to gain comprehensive insights into the relationship between gamified learning and critical thinking. Findings: The findings suggest that gamified mobile learning can indeed be a powerful tool for fostering critical thinking skills. By harnessing the motivational power of games, educators can create dynamic learning environments that inspire learners to think critically, solve problems, and achieve deeper understanding. Gamified challenges, decision-making scenarios, collaborative experiences, adaptive pathways, and immersive narratives provide learners with meaningful learning experiences that promote active engagement and reflection. Conclusion: Overall, gamified mobile learning has the potential to revolutionize education by cultivating the skills and dispositions necessary for success in the 21st century. Keywords: critical thinking skills, education, gamified learning, thematic analysis.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202418